Social Acceptance in Inclusive Classrooms: The Role of Teacher Attitudes Toward Inclusion and Classroom Management - Garrote, Ariana; Felder, Franziska; Krähenmann, Helena; Schnepel, Susanne; Sermier Dessemontet, Rachel; Moser Opitz, Elisabeth (Frontiers in Education, 2020)
Social acceptance is vital to students’ development. Being rejected by classmates can result in negative socio-emotional and academic outcomes. Finding relevant factors to be able to effectively support student social acceptance is especially challenging in inclusive classrooms because of the high heterogeneity of the student group. There is evidence that social acceptance is determined by the social behavior of students. In addition, current research suggests that affect-motivation dispositions, such as teacher attitudes, are related to teaching practices, which in turn are associated with student outcomes. This longitudinal study examines, on an individual level, the relationship between social behavior and the social acceptance of students. On a classroom level, the extent to which a teacher’s attitudes towards the inclusion of students with special educational needs affects their classroom management (i.e., implementation of clear rules and successful time management) is analyzed. In addition, the effect of teacher attitudes towards inclusion and classroom management on social acceptance in the classroom is investigated. The social acceptance of a sample of 580 students in 34 inclusive classrooms was assessed at the beginning and the end of the school year. In addition, student social behavior was rated by peers at the beginning of the school year. Teachers (N = 34) were asked about their attitudes towards inclusion at the beginning of the school year. One mathematics lesson in each classroom was videotaped to assess the teachers’ classroom management practices. Multilevel structural equation models revealed a positive relationship between student social behavior and their social acceptance in the peer group. Contrary to expectations, teachers’ attitudes towards inclusion did not predict their classroom management practices (i.e., implementation of clear rules and successful time management). As hypothesized, teachers’ classroom management predicted the level of social acceptance in the classroom, whereas teachers’ attitudes towards the inclusion of students with special educational needs did not. The study results are discussed in light of previous findings and implications for teacher education are described.